Data Identification of Cirebon Batik West Java Source of Strength Geographical Indication - Komarudin Kudiya; Miranda Risang Ayu (Kosmik Hukum, 2020)
In the history of batik in Indonesia, We used to know that batik is identified with Javanese culture. In addition, the use of batik cloth is limited to the royal court with a variety of very strict rules. But in its development, batik is no longer owned by Javanese, batik has now become one of the "national clothes" of Indonesia that is used by Indonesians throughout the archipelago on various occasions. In West Java batik has grown and developed in 27 regencies/cities spread from the eastern part of the Cirebon district to the western of West Java, Depok. There are potential characteristics and excellences from each region in West Java that people could not find in other regions. The uniqueness and characteristics of batik in certain area are part of the protection system of geographical indications that identify an area of the country, as the origin region of the product, where the reputation, quality and characteristics of related products are largely determined by geographical factors in the region. The need for a complete and accurate identification in the protection of Geographical Indications is very important considering batik products in West Java have enormous potential that can be protected as part of Geographical Indications (IG) which can be used as marketing tools in the world of commerce, both at the national and international level.Keywords: Cirebon Batik, Geographical Indication, Identification